Butylated starch alleviates polycystic ovary syndrome by stimulating the secretion of peptide tyrosine-tyrosine and regulating faecal microbiota. (1st July 2022) - He, Yufeng; Shi, Liuting; Qi, Yajin; Wang, Qianqian; Zhao, Jianxin; Zhang, Hao; Wang, Gang; Chen, Wei
Abstract: Polycystic ovary syndrome (PCOS) is an endocrine disorder that affects women of reproductive age. Resistant starch can be fermented by gut microbes then produce short-chain fatty acids (SCFAs). It was reported SCFAs might play a key role in gut microbiota-dependent therapy of PCOS. However, the effects of resistant starch on PCOS symptoms have not yet been investigated. Here, maize starch was acylated with specific SCFAs. Our results indicated that acylated starch can release acetate, propionate, and butyrate into the caecum and colon. Treatment with butylated starch (BS) alleviated abnormal ovarian morphology, metabolic disorders, and sex hormone imbalance in letrozole-treated rats, whereas treatment with acetylated starch and propylated starch did not exhibit such effects. Furthermore, BS stimulated the secretion of peptide tyrosine-tyrosine into the serum by activating a G protein-coupled receptor, GPR41, which further affected disease phenotypes. In addition, compared with caecal microbiota, faecal microbiota was more affected by BS. Butyrate-producing microbes were enriched in faeces after BS treatment and may have helped further to relieve PCOS symptoms. Graphical abstract: Unlabelled Image